Drivers of Customer Equity in Acquiring and Retaining Customers in the South African Automobile Industry - Barron, Brandon (My University, 2011)
The recent global financial crisis has made customers think twice before purchasing anything that involves a substantial financial expense. Availability of credit from financial institutions makes purchasing of expensive goods like houses and motor vehicles much more difficult. Companies have realized this fact and now need to target their marketing activities to persuade customers to make those purchases that they might not be that willing to undertake considering these restrictions and added hassle. This research looks at the following question. What are the drivers of customer equity in acquiring and retaining customers in the South African luxury automotive industry? The Customer Equity driver model was targeted to see which of the drivers (Value, Brand and Relationship equity) is seen as more important to the customer when deciding to purchase a vehicle. A sample of 95 customers of 3 Series BMW„s and 32 BMW dealer staff were used in gathering the required data. All respondents completed an online questionnaire on importance ratings and performance against these ratings for certain competitors of BMW. The responses were analyzed using descriptive analysis as well as statistical methods of factor and principal component analysis. The results were interpreted to answer the questions posed and to see which Customer Equity (CE) drivers and their respective levers customers see as more important in this economic down turn. The results showed that the Value equity driver is seen as the most important by customers and dealers followed by Relationship equity and Brand equity drivers respectively. The Value equity lever of vehicle build quality was seen as the most important lever by both the customers and dealers. In comparing BMW‟s performance against the CE drivers it can be seen that BMW is performing well in Relationship and Brand equity driver areas but they still need to improve their Value equity driver.
MBA - WBS
Keywords: Customer equity; Customer retention; Automobile industry